FRAMING ANALYSIS IN MEDIA INFORMATION ABOUT THE CASE OF SETYA NOVANTO RELATED TO PROCUREMENT E-KTP (KOMPAS AND DETIK) - Siti Masitoh; Syifa Fauzia Rahmah; Teti Sobari (IKIP Siliwangi, 2019)
The recent case of the E-KTP procurement project has attracted a lot of public attention. In this study, the author focused on the object of research on the involvement of the PDI-P Party in this mega corruption case. The PDI-P party is President Jokowi's bearer party in the 2014 presidential election. In this case, Novanto stated that he was involved in this case and even became the main suspect in the E-KTP procurement project. Language tools used as a method in analyzing the object of this research are Framing Analysis. Basically, framing is a method for viewing media telling stories about events. News that contains framing does not mean that the news is false news. In framing a news, the information obtained by a journalist is processed by constructing the contents of the news and presenting it to the public. Some are highlighted and some are excluded. This depends on how journalists interpret an event, and how a fact from that information is written.Keywords: Framing Analysis, E-KTP Procurement Project